2013
DOI: 10.1371/journal.ppat.1003779
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Analysis of Murine Macrophages Infected with Different Toxoplasma Strains Identifies Novel Regulation of Host Signaling Pathways

Abstract: Most isolates of Toxoplasma from Europe and North America fall into one of three genetically distinct clonal lineages, the type I, II and III lineages. However, in South America these strains are rarely isolated and instead a great variety of other strains are found. T. gondii strains differ widely in a number of phenotypes in mice, such as virulence, persistence, oral infectivity, migratory capacity, induction of cytokine expression and modulation of host gene expression. The outcome of toxoplasmosis in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
118
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(128 citation statements)
references
References 82 publications
5
118
0
5
Order By: Relevance
“…T . gondii infection, moreover, does not elicit type 1 IFNs and their potential disease-exacerbating comorbidities [33]; a phenomenon observed in the course of many infections and an important consideration, particularly in the context of STAT2 deficiency and hence disrupted type 1 IFN signaling [34]. At first, WT- and STAT2-deficient mice were injected with IFN-γ or PBS (controls), before peritoneal macrophages were collected for ex vivo infection experiments with T .…”
Section: Resultsmentioning
confidence: 99%
“…T . gondii infection, moreover, does not elicit type 1 IFNs and their potential disease-exacerbating comorbidities [33]; a phenomenon observed in the course of many infections and an important consideration, particularly in the context of STAT2 deficiency and hence disrupted type 1 IFN signaling [34]. At first, WT- and STAT2-deficient mice were injected with IFN-γ or PBS (controls), before peritoneal macrophages were collected for ex vivo infection experiments with T .…”
Section: Resultsmentioning
confidence: 99%
“…In support of this hypothesis, it has been shown that T. gondii infection of fibroblasts pre-stimulated with IFNγ triggers a stronger type I IFN response than infection of untreated fibroblasts 35 . ISG-encoded GTPases are essential for controlling the infection both ex vivo 42,44 and in vivo, as mice lacking genes of the IRG family or genes encoding several GBPs are more susceptible to T. gondii infection than their wild-type counterparts 42,[45][46][47] .…”
mentioning
confidence: 88%
“…1c) in macrophages infected with less virulent T. gondii type II strains but not in macrophages infected with virulent type I strains 60 . This protein is highly polymorphic, and differences in its amino acid sequence and its expression levels seem to explain the variations observed between distinct T. gondii strains concerning the activation of pro-inflammatory host genes 35 . GRA15 is secreted from dense granules and traffics to the host cytosol during the invasion and intracellular growth of PV-enclosed T. gondii parasites.…”
Section: Bacterial Pathogensmentioning
confidence: 99%
See 2 more Smart Citations